Perubahan Sikap Mad’u Mahasiswa KPI Angkatan 2022 dan Penggunaan Instagram sebagai Media Dakwah - Salwa Intan Fatikah; Supriadi Supriadi; Muhammad N. Abdurrazaq (Badan Penerbit STIEPARI Press, 2025)
This thesis examines the influence of Islamic preaching (dakwah) through Instagram on attitude changes among students of the Islamic Communication and Broadcasting Study Program (KPI), class of 2022, at Al-Zaytun Islamic Institute of Indonesia (IAI AL-AZIS), Indramayu. The main phenomenon explored is the use of Instagram as a medium for dakwah and the extent to which it can trigger changes in students’ attitudes. The study aims to analyze cognitive, affective, and conative attitude changes resulting from exposure to dakwah content on Instagram, as well as to understand students’ preferences in selecting effective dakwah content. The research employs a qualitative descriptive-analytical approach with data collection techniques including in-depth interviews, participatory observation, and documentation. Informants were selected using purposive sampling, and the data were thematically analyzed to identify patterns and meanings derived from students’ experiences. The findings show that Instagram is perceived as an effective medium of dakwah among KPI students. They prefer concise, visual, and easy-to-understand content such as short videos, reels, quotes, and carousels. The main factors attracting students are persuasive delivery styles, the relevance of themes to their daily lives, and appealing visual designs. Their motivation to follow dakwah accounts is primarily driven by the need for inspiration, motivation, and spiritual support. The impact of Instagram-based dakwah is evident in cognitive (religious knowledge), affective (religious feelings and attitudes), and conative (religious practices) aspects. However, these changes tend to be temporary and inconsistent. Thus, although Instagram is effective as a medium of preaching dakwah, both internal and external reinforcement are required to ensure more sustainable impacts